Collaboration and networking in education - Muijs, Daniel (Springer Netherlands, 2011)
Collaboration and networking have recently come to the fore as major school improvement strategies in a number of countries. A variety of initiatives, from government and other agencies, have encouraged collaboration and led to a lot of practical activity in this area. However, at present there are no texts in education that explore collaboration and networking from both a theoretical and practical perspective. In this book, we aim to provide a theoretical background to educational collaboration, drawing on research and theory in policy studies, psychology and sociology, leading ultimately to a typology of networks. This theoretical base will be tested in the discussion of a number of case studies referring to specific initiatives such as the Federations programme, multi-agency collaboration and Networked Learning Communities. Lessons for practice will be drawn and presented in terms of factors internal and external to the school. The key issue of network leadership will be addressed here as well.